The Practice of Ijbar Rights in Marriage, a Review of the Compilation of Islamic Law (Case Study in Sambung Village, Gajah Subdistrict, Demak Regency) - Cahya Ma’rifatul Yahya; Inna Fauziatal Ngazizah (QURU’: Journal of Family Law and Culture, 2024)
This research was motivated by the practice of ijbar rights in marriage that occurred in Sambung Village, Gajah District, Demak Regency. Basically, the right of ijbar is seen as a form of protection and love of a guardian towards his daughter. However, in practice, marriage is carried out by a guardian (parent) for their child without considering the child's willingness. The concept of the right to ijbar is considered to be contrary to the principle of justice for a child without obtaining the consent of the person concerned. The first aim of this research is to find out how the right of ijbar is practiced in marriage. Second, to determine the impact of the practice of the right to ijbar. Third, namely to find out how the Compilation of Islamic Law (KHI) reviews the practice of the right to ijbar. This research is research carried out directly in the field (field research with 10 informants in this research, namely 3 husband and wife couples, 3 parents, and 1 religious figure. This research uses a qualitative approach that describes the problems of the practice of ijbar rights that occur in the village Sambung, Gajah District, Demak Regency, by interviewing informants, recording and analyzing data obtained regarding the practice of ijbar rights. The results of this research, firstly, the practice of guardian rights is often based on girls' feelings of unwillingness and on average girls who are forced to marry are still very young. Assumptions that have influenced people's understanding have led to the practice of the right of ijbar in Sambung Village, which assumes that if a woman or girl has reached the legal age for marriage, it is best to get married immediately. Second, the impact of a marriage with the right of ijbar is that the household is not harmonious, parents always interfere in the child's household, and this triggers divorce. If the practice of the right of ijbar meets the provisions of the Compilation of Islamic Law as stated in article 16, then a marriage must be based on the consent of the prospective bride and groom.